Specificity of mythopoetical images in the novel O. Bokeev «Snow Girl» (Eurasian Journal of Philology Science and Education, 2016)
The article discusses the implication of the story mythopoetical Kazakh writer O. Bokeev «Snow Girl». The system works the images seen at the junction of real, every day and mythological narratives plans. Both plans are reflected in each other, as in a mirror, both contrasted and combined with complex system of correspondences. Analyzed in detail the philosophical aspects of the author’s reflections on the causes and nature of human cruelty, about the causes of degradation of the society on a spiritual level and the factors that could stop such events. We study the metaphorical and folklore and mythological images to help create mythopoetical subtext works – Snow girl, man-beast, and others. This arrangement enhances semantic-term work, thus complicating and connect it to the powerful imagery of mythological context of different nations. Wire must be parallel within the above comparison of the images in the Altai, Japanese, Kazakh folklore. We investigate the figurative motivic complex story O. Bokeev in which particular importance is the leitmotif of the tragic fate of the girl who suffered the fault villain Conca. The conclusion is that the myth of O. Bokeev have means of concentration of the world around man and within him.
Keywords: myth; mythopoetics; image; plot; motive; folklore; synthesis.